2021
DOI: 10.3389/fcell.2021.666508
|View full text |Cite
|
Sign up to set email alerts
|

The Core Promoter Is a Regulatory Hub for Developmental Gene Expression

Abstract: The development of multicellular organisms and the uniqueness of each cell are achieved by distinct transcriptional programs. Multiple processes that regulate gene expression converge at the core promoter region, an 80 bp region that directs accurate transcription initiation by RNA polymerase II (Pol II). In recent years, it has become apparent that the core promoter region is not a passive DNA component, but rather an active regulatory module of transcriptional programs. Distinct core promoter compositions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 144 publications
(172 reference statements)
0
14
0
Order By: Relevance
“…Similarly, in our study, 2278 bp, 1917 bp, and 1989 bp zip10 , zip13 and zip 14 promoters of P. fulvidraco were cloned. The earlier studies suggested that the core promoters of genes played central roles in initiating the transcriptions [ 51 , 52 ]. In our study, we predicted one GC-box (SP1), one CCAAT-box (NF-Y), and one TATA-box in the core region of the zip10 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, 2278 bp, 1917 bp, and 1989 bp zip10 , zip13 and zip 14 promoters of P. fulvidraco were cloned. The earlier studies suggested that the core promoters of genes played central roles in initiating the transcriptions [ 51 , 52 ]. In our study, we predicted one GC-box (SP1), one CCAAT-box (NF-Y), and one TATA-box in the core region of the zip10 promoter.…”
Section: Discussionmentioning
confidence: 99%
“…These promoters have unique features that allow selective regulation during development. According to the current classification of eukaryotic promoters (reviewed in Ngoc et al, 2019;Sloutskin et al, 2021), P1 is a dispersed promoter with four non-canonical TSS, while P2 is a focused promoter with a DPE box (Juven-Gershon et al, 2008), a motif recognized by the basal transcription machinery factor TFIID subunits, TAF6 and TAF9 (Burke & Kadonaga, 1996. This complex gene structure and expression have an effect on the production and dosage of different Antennapedia isoforms.…”
Section: Antp Gene and Protein Structuresmentioning
confidence: 99%
“…A promoter is a DNA sequence that controls gene expression; it contains binding sites for transcription factors and RNA polymerases [ 19 ]. The number and spectrum of transcription factors involved and the position of their binding sites relative to the transcription start site (TSS) determine the frequency of binding of the transcription complex and, therefore, the efficiency of gene expression that corresponds to such a characteristic of the promoter as “promoter strength” [ 19 , 20 , 21 ]. The versatility or tissue-specificity of a promoter (the ability to provide gene expression in a wide range of cells or in a certain type of them) is ensured by the presence of binding sites for versatile or tissue-specific transcription factors, respectively [ 19 , 20 , 21 ].…”
Section: Cis-/transgene Expression In Cell Lines Genetically Encoded ...mentioning
confidence: 99%
“…The number and spectrum of transcription factors involved and the position of their binding sites relative to the transcription start site (TSS) determine the frequency of binding of the transcription complex and, therefore, the efficiency of gene expression that corresponds to such a characteristic of the promoter as “promoter strength” [ 19 , 20 , 21 ]. The versatility or tissue-specificity of a promoter (the ability to provide gene expression in a wide range of cells or in a certain type of them) is ensured by the presence of binding sites for versatile or tissue-specific transcription factors, respectively [ 19 , 20 , 21 ]. A constitutively active promoter contains binding sites for transcription factors that are permanently active in a certain cell type, which ensures constant gene expression.…”
Section: Cis-/transgene Expression In Cell Lines Genetically Encoded ...mentioning
confidence: 99%
See 1 more Smart Citation